2006: STATUS OF TSUNAMI SCIENCE RESEARCH AND FUTURE DIRECTIONS OF RESEARCH - Barbara H. Keating (Science of Tsunami Hazards, 2006)
In 2005, Dr. Robert Wiegel compiled “Tsunami Information Sources”. The compilation has been made available via a website and has been published as an issue in Science of Tsunami Hazards. The compiled references have been assigned keyword descriptions, and compiled in order to review the breath and depth of Tsunami Science publications.The review indicates that tsunami research involves eight major scientific disciplines: Geology, Seismology, Tsunami Science, Engineering, Disaster Management, Meteorology and Communications. These disciplines were subdivided into many topical subjects and the results were tabulated.The topics having the largest number of publications include: tsunamigenic earthquakes, numerical modeling, field surveys, engineering models, harbor, bay, and canal modeling and observations, energy of tsunamis, workshops, tsunami warning centers, instrumentation, tsunami catalogs, tsunami disaster mitigation, evaluation of hazards, the aftermath of tsunamis on humans, and AID provided to Tsunami Damaged Communities.Several areas of research were identified as likely directions for future research, including: paleotsunami studies, risk assessments, instrumentation, numerical modeling of earthquakes and tsunami, particularly the 2004 Indian Ocean event. There is a dearth of recent publications available on tsunami hazards education for the general public.